Smoking Prevalence, Nicotine Dependence, and Impulsivity in Obsessive-Compulsive Disorder - Tan, Oguz; Koroglu, Ayce. F. (SPRINGER, 2020)
This study compared obsessive-compulsive disorder (OCD) and control participants in terms of smoking prevalence, nicotine dependence, and impulsivity. Data derived from 314 OCD patients and 319 control participants revealed that smoking prevalence did not differ between the two groups yet the severity of nicotine dependence was higher among OCD patients. OCD group also exhibited greater total, cognitive, and non-planning impulsivity than controls, and this pattern of differences was also evidenced in OCD and control current and never smokers. In both OCD and control group, modest positive associations were found between impulsivity and nicotine dependence, yet the relationships were relatively stronger for the OCD group. Results are discussed in terms of how smoking, dependence, and impulsivity might articulate to play a role in obsessive-compulsive disorder.
Keywords: Smoking; Nicotine; Dependence; Obsessive-compulsive disorder; Impulsivity; CIGARETTE-SMOKING; ANXIETY DISORDERS; PERSONALITY; SPECTRUM; SCALE; Psychology; Substance Abuse; Psychiatry